The Implementation of Student Discipline Through School Rules - Dewi, Isna Sofia; Hendracipta, Nana; Syachruroji, Ahmad (Universitas Pendidikan Ganesha, 2021)
The number of character problems experienced by Indonesia strengthens the urgency of planting and implementing character education. One of the necessary character plantings is the character of discipline. This study analyzes the impact of teaching student discipline characters through school rules. This study uses descriptive qualitative methods with data collection techniques used in this research using observation, interviews, and documentation. Sources of data in this study came from the principal, 5th-grade teaching teachers, and students. The study results indicate that the cultivation of disciplinary character is carried out through school rules in the early stages, namely the preparation of planning and development of disciplinary characters. Facilities and infrastructure provided can also support the inculcation of students' disciplined characters. In addition, teachers and principals also always provide concrete examples of the behavior of disciplined characters. In teaching the character of discipline, of course, there are obstacles and obstacles. However, the principal and teachers communicate and work together with the students' parents to overcome the obstacles. This research implies that it can explain the impact of planting student discipline characters through school rules to contribute to student and school achievement.